Medium to Long Term Follow-Up of Treated Hypertensive Mediated Heart Disease - Piskorz, Daniel (High Blood Press Cardiovasc Prev, 2021)
INTRODUCTION: Hypertensive mediated heart disease is the consequence of anatomical and functional changes in cardiovascular system. The benefits on left ventricular (LV) diastolic impairment and remodeling of hypertension treatment are well established. AIM: To evaluate LV structure, systolic and diastolic function of treated hypertensive patients on a medium to long term follow-up. METHODS: Prospectively observational cohort study. Hypertensive patients over 18 years, ultrasound evaluation of LV structure and diastolic and systolic function, follow-up at least once a year. Diastolic function assessed following recommendations of the American Society of Echocardiography and the European Association of Cardiovascular Imaging. RESULTS: 285 patients, mean follow up of 1731 ± 952 days. Sample mean age 56.3 ± 12.5 years, 166 patients (58.3%) were males. Baseline blood pressure 147.8 ± 19/86.8 ± 11 mm Hg, 5 years blood pressure 134.4 ± 15.7/79 ± 9 mm Hg (p < 0.005 SBP and p < 0.01 DBP). Baseline fixed dose combinations 115 patients (40.4%), follow-up 53.1% (p < 0.05). LV remodeling was detected in 88 patients (30.9%) vs. 30.1% at 5 years (p = NS). The frequency of an E/e′ ratio > 14 was reduced from 38 patients (13.3%) to 3.6% (p < 0.001), e′ septal velocity < 7 cm/sec or e′ lateral velocity < 10 cm/sec was reduced from 38.6% (110 patients) to 19.3% (p < 0.001). Baseline normal diastolic function was detected in 85.6% (244 patients) and 94% at the end of the follow-up (p < 0.02). CONCLUSIONS: In this observational cohort followed by a mean of 5 years, the main benefit of hypertension treatment was the prevention or regression of diastolic dysfunction.